Changes in Graves’ Ophthalmopathy after Radioiodine and Anti-Thyroid Drug Treatment of Graves’ Disease from 2 Prospective, Randomized, Open-Label, Blinded End Point Studies - Chen, D. Y.; Schneider, P. F.; Zhang, X. S.; Luo, X. Y.; He, Z. M.; Chen, T. H. (Experimental and Clinical Endocrinology & Diabetes, 2014)
A significant association between radioiodine therapy (RIT) and the development or the worsening of pre-existing Graves’ ophthalmopathy (GO) has been reported. This post-hoc analysis of 2 studies attempted to describe the changes observed in pre-existing or new-onset GO following RIT with the goal of euthyroidism rather than hypothyroidism and to describe the relationship GO changes and the final outcome.In 2 prospective, randomized open-label blinded endpoint trials, patients received radioiodine alone; or, patients received radioiodine or antithyroid drug therapy (ATD). The severity and activity of GO were assessed during a 9–12-year follow-up. The study end points in study 1 were euthyroidism, hyperthyroidism, hypothyroidism, and changes in GO. In study 2, the end points were euthyroidism, hyperthyroidism, hypothyroidism, relapse, and changes in GO.Both RIT and ATD were associated with worsening GO and new-onset GO. Both RIT and ATD led to similar aggravation of pre-existing GO or the development to new-onset GO. After RIT or ATD, the euthyroid patients (without levothyroxine substitution) demonstrated an improvement in GO, with 78–89% patients with preexisting GO exhibiting improvement, whereas hyperthyroid, hypothyroid and relapsed patients had worsening or new-onset GO.Thyroid function is a dominant risk factor. Thyroid function may be the most important determinant in worsening or new-onset GO in both the natural disease course and in treated patients, independent of the kind of treatment. Therefore, we recommend euthyroidism as a goal of treatment.
Keywords: Graves’ ophthalmopathy; euthyroidism; hyperthyroidism; hypothyroidism; radioiodine